Bioethics, Human Rights and COVID-19 - Bellver, Vicente (Cuadernos de bioética, 2020)
In this paper present, from a bioethical perspective, a reflection on how to reconcile efforts to combat the COVID-19 pandemic with the safeguard of human rights. To do this, I develop three points. First, the regulatory framework that justifies the restriction or suspension of rights in the face of serious threats to public health. Second, the declarations of the international bioethics committees on the way in which human rights should be protected during public health crisis. And third, a review of the main rights threatened both by the public health crisis and by the means adopted to combat it. Before going into each of these points, I offer a preliminary note to clarify certain legal concepts and underline the need to overcome disjunctive approaches in considering human rights.